Happy Smile of a New-Born Infant with Cleft Lip and Cleft Palate - Istien Wardani; Dyah Ayu (Denta Journal Kedokteran Gigi, 2022)
Background: Cleft palate of the new-born infants with or without cleft lip, are recognized to be at risk of feeding difficulties, making it difficult to maintain adequate nutrition, and also interfere the speech function and the parents also their psychological growth. Purpose: Surgical closure of the cleft lip may be accomplished shortly after birth to relieve the parents’ anxiety as long as the general rules “ triple tens ” ( more than : 10 week of age, 10 pounds of body weight, 10 grams of haemoglobine ) that is frequently used in determining optimum timing for lip closure must be fulfilled. Case Report: Female baby at age 5 days, who was referred  to pediatric dentistry clinic dr. Ramelan Naval Hospital Surabaya with parents complaining that their baby was born with cleft lip and palate and could not drink breast milk, easily choked, so they had to depend on the sonde. Case management: A maxillary feeding plate (=MFP) was made to close the cleft palate and regenerate the function of chewing and swallowing so that the infant obtains good nourishment and gain body weight until the palatal cleft closure operation. Conclusion: After the closure, her mother and family are psychologically able to prepare comprehensive protection for the child so that they too feel comfortable and confident. Smile can represent 80% of communication. When children feel comfortable because they can freely smile, this smile can attract other people to make it easier to adapt and socialize.